IMPROVING THE STUDENTS READING COMPREHENSION IN NARRATIVE TEXT THROUGH PATTERNED PARTNER READING - Ardiana Ardiana (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2015)
This research aimed to find the use of Patterned Partner Reading strategy improve the students reading comprehension at the SMP Muhammadiyah Limbung. The researcher used A Classroom Action Research (CAR). The researcher had conducted two cycles, where each cycle consisted of four meetings. This classroom action research was one at SMP Muhammadiyah Limbung. As subject in this research was the second class with students’ number as about 30 students consist of 7 man and 23 women. The instruments were observation sheet and test sheet. The research findings indicated that the application of patterned partner reading strategy was effective and significant in improving the students’ reading skill especially students’ reading comprehension. It was proved that the mean score of D-Test was 60.8, Cycle I 75.5 and after conducted Cycle II improved to 93 And based of mean score of students’ reading comprehension during two cycle researcher found percentage improvement that is from D-Test to Cycle I is 24.17% and from Cycle I to Cycle II is 23.17 and D-Test to Cycle II 52.96%. It means that there was the improvement of students’ reading comprehension on learning process.